Edukasi Ilmu Hukum untuk Anak Sekolah Dasar Guna Pencegahan Bullying - Sri Rumada Sihite (Lembaga Pengembangan Kinerja Dosen, 2025)
The school actively participates in coaching and monitoring all student activities to avoid bullying, especially against educators. All student activities can also be reviewed in the coaching process, and parents are expected to provide guidance to prevent bullying that ultimately harms them. Ideally, this community service activity is to provide material about bullying. The purpose of this socialization activity is to help children at GKPS Elementary School in accordance with the character of a noble generation. In addition, this activity has the aim of being a synergy between teacher partners and schools in developing learning, and encouraging creativity and innovation in Hinaa. So that increased literacy and numeracy are achieved and bullying can not occur in elementary schools.